Electronic and Thermoelectric Properties on Rutile SnO2 Under Compressive and Tensile Strains Engineering - Budi Adiperdana; Nadya Larasati Kartika; Irwan Ary Dharmawan (Jurnal Elektronika dan Telekomunikasi, 2022)
SnO2 has the potential to be an environmentally friendly thermoelectric material. To obtain the optimum properties of this material, strain engineering is used to investigate the electronic and thermoelectric properties. In this study, we used compressive and tensile strains with -5%, -2%, 0%, 2%, 5%, and 10% in three schemes; they are triaxial (ɛabc), biaxial (ɛab), and uniaxial (ɛc) strains. All model structures are calculated based on density functional theory (DFT) with several exchange-correlation functionals. The presented results show that strain engineering enhances the Seebeck coefficient for a compressive strain parameter since the energy gap between the conduction and valence band increased due to the strong covalent bonding at the conduction band. From several comparisons in bandgap and thermoelectric properties calculation between PBEsol and PBE0, this study suggests that PBE0 is effectively used to calculate the energy gap. Meanwhile, for thermoelectric properties, PBEsol gave the best-estimated value. In addition, this study explained that the largest or the smallest bandgap could be achieved by varying strain simply on the c-axis as the optimum manipulation of the SnO2 structure. Furthermore, this paper also revealed that the simulation strategy could be determined from the desired result, whether to enhance the Seebeck coefficient or the electrical conductivity by manipulating the ab-axis and the c-axis, respectively.